Tinjauan Customer Life Cycle Pada PT Sumber Aneka Inovasi - Pratama, Ananda; Panduwangi, Morita; Gendalasari, Gen Gen (Program Vokasi dan LPPM IBI Kesatuan, 2025)
In today’s increasingly competitive market, companies must adopt effective strategies to retain customer loyalty. A critical step in developing such strategies is understanding the Customer Life Cycle (CLC) to identify and acquire potential customers aligned with organizational needs. This study aims to: (1) examine the implementation of the CLC at PT Sumber Aneka Inovasi; (2) identify obstacles in its implementation; and (3) analyze the company’s efforts to overcome these challenges. The findings reveal that PT Sumber Aneka Inovasi retains customers by offering facilities and discounts to transform regular buyers into brand advocates. However, challenges arise in acquiring potential customers due to the broad scope of available data, which complicates the identification process. To address this, the company applies segmentation and targeting strategies to more effectively reach potential customers.